2022
DOI: 10.1007/s00203-022-02823-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and evolutionary analysis of Orientia tsutsugamushi in eastern Indian population

Abstract: Scrub typhus is a bacterial zoonotic acute febrile illness (AFI) caused by the obligate intracellular bacterium Orientia tsutsugamushi , which is an antigenically diverse strain frequently observed in the tropical region of Southeast Asian countries. The recent investigation was conducted to delineate the genotype identification of Orientia tsutsugamushi predominating in the eastern zone of India such as Odisha to decipher its strain type, and evaluate its diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…7,[23][24][25] A study from eastern region of India reported the occurrence of Kato as the single most prevalent strain. 19 In a study from North India, Gilliam has been identified to be the most common genotype, followed by Karp-like strains. 26 Kato-like strains have been observed to be widespread throughout the country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,[23][24][25] A study from eastern region of India reported the occurrence of Kato as the single most prevalent strain. 19 In a study from North India, Gilliam has been identified to be the most common genotype, followed by Karp-like strains. 26 Kato-like strains have been observed to be widespread throughout the country.…”
Section: Discussionmentioning
confidence: 99%
“…40 The possible reason for increase in ST prevalence in urban area may be due to globalization, climate change, larger influx of population into urban region, and deforestation of adjacent rural region for city expansion led to displacement of vectors as well as rodents from one place to other 41 ; that may widen the endemic area further. 19 Scrub typhus is largely under-diagnosed in India as the clinical symptoms of ST are nonspecific and mostly indistinguishable from other tropical febrile illness like malaria, dengue fever, typhoid fever and leptospirosis. The presence of eschar is an important clue for the initial diagnosis of ST. 42,43 However, their presence varies widely in the endemic region, ranging from 7-97%, 44 and this difference may be influenced by the factors like skin color, physical examination done by the investigator and strain variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was endemic to the Asia–pacific region known as the “tsutsugamushi triangle”, but many reports suggest that it is spreading all over the world including Dubai, United Arab Emirates, Chile, Peru, and Africa and cause a severe public health problem throughout the globe (Xu et al 2017 ). Though scrub typhus is becoming a common life-threatening and re-emerging disease that accounts for one million cases every year with a high mortality rate, still, it is neglected and underdiagnosed (Luce-Fedrowet al 2018 ; Swain et al 2022 ).…”
Section: The Bacteriummentioning
confidence: 99%
“…Generally, chiggers are only active within a certain area of their breeding site. However, alterations in human behavior and social environment lead to migration of vectors and hosts from one location to another, which may spread pathogens to more distant areas and cause disease transmission (9)(10)(11). ST is widespread in the "tsutsugamushi triangle" area ranging from Afghanistan in the west to the east coast of Russia in the north to northern Australia in the south (12).…”
Section: Introductionmentioning
confidence: 99%